Imaging brain tumors with ferumoxtran-10, a nanoparticle magnetic resonance contrast agent. Issue 6 (November 2005) - Murillo, Tulio P; Sandquist, Chloe; Jacobs, Paula M; Nesbit, Gary; Manninger, Sandor; Neuwelt, Edward A
Background: Ultrasmall superparamagnetic particles of iron oxide are magnetic resonance contrast agents that are gaining use in the CNS. These agents accumulate in phagocytic cells such as reactive astrocytes and macrophages. Aim: We aimed to describe the use of ferumoxtran-10, an ultrasmall superparamagnetic particle of iron oxide, in brain tumor imaging and detail the results in a series of 55 patients with intracranial tumors. Results: In 19 out of 34 glial tumors, ferumoxtran-10 enhanced as much as (n = 9) or more than gadolinium (n = 10). In the nonglial tumors group, seven out of 22 tumors enhanced as much as (n = 2) or more than gadolinium (n = 5). Conclusion: Ferumoxtran-10-enhanced magnetic resonance can add information to gadolinium-enhanced magnetic resonance, especially in identifying the inflammatory component and blood––brain barrier compromize involved in infiltrating malignant brain tumors.